THE IMPLEMENTATION OF TECHNICAL APPLICATIONS TO THE TEACHING OF APPLIED MATHEMATICS - VAGASKA, Alena; GOMBAR, Miroslav; Jan, KMEC (Trends in education, 2012)
The possibilities of the implementation of technical applications as well as ICT to the teaching of Applied Mathematics are presented in the article with the aim to contribute to the effectiveness of technical education at the faculties of technical universities.
Keywords: technical education; applied mathematics; mathematical modelling; numerical methods; ICT.